Co-infection of the four major Plasmodium species: Effects on densities and gametocyte carriage. - Aurel Holzschuh; Maria Gruenberg; Natalie E Hofmann; Rahel Wampfler; Benson Kiniboro; Leanne J Robinson; Ivo Mueller; Ingrid Felger; Michael T White (Public Library of Science (PLoS), 2022)
Background Co-infection of the four major species of human malaria parasite Plasmodium falciparum (Pf), P. vivax (Pv), P. malariae (Pm), and P. ovale sp. (Po) is regularly observed, but there is limited understanding of between-species interactions. In particular, little is known about the effects of multiple Plasmodium species co-infections on gametocyte production. Methods We developed molecular assays for detecting asexual and gametocyte stages of Pf, Pv, Pm, and Po. This is the first description of molecular diagnostics for Pm and Po gametocytes. These assays were implemented in a unique epidemiological setting in Papua New Guinea with sympatric transmission of all four Plasmodium species permitting a comprehensive investigation of species interactions. Findings The observed frequency of Pf-Pv co-infection for asexual parasites (14.7%) was higher than expected from individual prevalence rates (23.8%Pf x 47.4%Pv = 11.3%). The observed frequency of co-infection with Pf and Pv gametocytes (4.6%) was higher than expected from individual prevalence rates (13.1%Pf x 28.2%Pv = 3.7%). The excess risk of co-infection was 1.38 (95% confidence interval (CI): 1.09, 1.67) for all parasites and 1.37 (95% CI: 0.95, 1.79) for gametocytes. This excess co-infection risk was partially attributable to malaria infections clustering in some villages. Pf-Pv-Pm triple infections were four times more frequent than expected by chance alone, which could not be fully explained by infections clustering in highly exposed individuals. The effect of co-infection on parasite density was analyzed by systematic comparison of all pairwise interactions. This revealed a significant 6.57-fold increase of Pm density when co-infected with Pf. Pm gametocytemia also increased with Pf co-infection. Conclusions Heterogeneity in exposure to mosquitoes is a key epidemiological driver of Plasmodium co-infection. Among the four co-circulating parasites, Pm benefitted most from co-infection with other species. Beyond this, no general prevailing pattern of suppression or facilitation was identified in pairwise analysis of gametocytemia and parasitemia of the four species. Trial registration This trial is registered with ClinicalTrials.gov, Trial ID: NCT02143934.